Financial Reporting and Characteristics of Impairment of Assets in Republic of Serbia - Hrapović, Kenan (Economic Annals, 2011)
This article analyzes the effectiveness of the short selling ban, and questions it with critiques from comparative empirical data. Authors have argued that the ban on short selling hit trading volumes but did not necessarily reduce market volatility. Today market regulators are seeking to rebuild a short selling policy that allows covered short selling while reducing the risk of market abuse. The reinforced framework must include rules and regulations that increase market efficiency, enhance the visibility of short selling to regulators and to investors, improve regulators’ responsiveness to market failures and periods of extreme volatility, and enforce anti-abuse laws consistently and judiciously. Although most regulators have allowed their short sale bans to lapse and seem to be thinking constructively about the form of future regulation, the dust has not settled on the short sale debate. As the events of the year 2010 outline, short selling regulations tend to mirror the capital markets they oversee. The author questions if the capital market in Montenegro is ready to lift the short selling ban and to allow speculative trading again.